A Review of Ammonia-Oxidizing Archaea and Anaerobic Ammonia-Oxidizing Bacteria in the Aquaculture Pond Environment in China - Lu, Shimin; Liu, Xingguo; Liu, Chong; Cheng, Guofeng; Zhou, Runfeng; Li, Yayuan (Frontiers in Microbiology, 2021)
The excessive ammonia produced in pond aquaculture processes cannot be ignored. In this review, we present the distribution and diversity of ammonia-oxidizing archaea (AOA) and anaerobic ammonia-oxidizing bacteria (AnAOB) in the pond environment. Combined with environmental conditions, we analyze the advantages of AOA and AnAOB in aquaculture water treatment and discuss the current situation of pond water treatment engineering involving these microbes. AOA and AnAOB play an important role in the nitrogen removal process of aquaculture pond water, especially in seasonal low temperatures and anoxic sediment layers. Finally, we prospect the application of bioreactors to purify pond aquaculture water using AOA and AnAOB, in autotrophic nitrogen removal, which can reduce the production of greenhouse gases (such as nitrous oxide) and is conducive to the development of environmentally sustainable pond aquaculture.